Ethnic secessionism in Iran: accusation or fact - Khorshidi, Majid; Lee, Yok Fee; Soltani, Fakhreddin (Canadian Center of Science and Education, 2010)
During recent one hundred years, all Iranian governments accused the ethnic groups on the secessionist aims, but the ethnic groups rejected these accusations. Simultaneous to the increase in the ethnic conflicts in the period of hard- liners in the past five years (mostly in non- violent form), accusations were strengthened. Through analysing the data collected by certain in-depth interviews with the Iranian ethnic groups’ elites; this article tends to verify the existence of secessionist aspires in the ethnic groups while they pursue their right of self-determination. Collected data emphasize that the ethnic groups have not pursued secessionist aims, and they seek their right on self-determination in the context of Iran. According to the data, almost the entire ethnic movements even two autonomists republic which were established in 1945-1946 in Kurdistan and Azerbaijan had no secessionist aims.